KOMBINASI PREDIKSI VOLUME SEDIMEN MENGGUNAKAN METODE HECRAS-USLE UNTUK MENDUKUNG KONSERVASI DAS LAMBIDARO PALEMBANG, SUMATERA SELATAN - Sultan, Masri nur; Farid, Mohammad; Prasetyo, Adi; Kusuma, Muhammad Syahril Badri; Natakusumah, Dantje Kardana (JURNAL SUMBER DAYA AIR, 2023)
Â Over the past ten years, flooding has been the most frequent problem in South Sumatra Province, Indonesia. As the capital of South Sumatra Province, Palembang City faces similar problems, where Lambidaro Watershed is the watershed with the highest 25-year potential flood discharge in Palembang City. One of the causes of flooding is the lack of river channel capacity related to land erosion in the watershed. This study aims to learn the prediction of sediment volume and efforts to reduce it in the Lambidaro watershed, Palembang City. This study uses two types of modeling, namely numerical models and empirical models. The numerical model uses the HEC-RAS 6.3.1 application, while the empirical model uses the USLE and SDR equations. The input parameters of the numerical model use some data derived from field measurements. The sediment concentration and observation discharge parameters were measured three times in September 2022. The grain size distribution parameters were sampled at three locations each once in August 2022, and the cohesive parameter was sampled at one location twice in August 2022. The result of the prediction of sediment volume by the numerical model is 1,421.86 m3/year. In contrast, the result of the prediction by the empirical model is 476,941.25 m3/year. Efforts to reduce the prediction of sediment volume USLE method are in the form of applying the intercropping method. The results of the conservation study show that the efforts made can reduce the volume of sediment by 17%. Keywords:Â Â Â Â Â Â sediment, flood, conservation, intercropping, LambidaroÂ